Pain, Cannabis Species, and Cannabis Use Disorders - Cohen, Nicole L. (J Stud Alcohol Drugs, 2016)
OBJECTIVE: The purpose of this study was to examine whether individuals who used medical cannabis for chronic pain were at increased risk for cannabis use problems compared with individuals who used medical cannabis for other reasons (e.g., anxiety, insomnia, and muscle spasms). An additional aim was to determine whether individuals who used cannabis for chronic pain, as well as those who reported greater within-group pain levels, demonstrated a species preference (i.e., sativa, indica, hybrids) and the extent to which species preference was associated with cannabis use problems. METHOD: Participants were 163 medical cannabis users (77% male), recruited from a medical marijuana dispensary in California, who completed assessments of medical cannabis use motives, history, preferences (species type), and problems, as well as current pain level. RESULTS: Individuals who used cannabis to manage chronic pain experienced fewer cannabis use problems than those who did not use it for pain; among those who used it for pain, the average pain level in the past week was not associated with cannabis use problems. Furthermore, individuals who used cannabis for chronic pain were more likely to use indica over sativa. Preference for indica was associated with fewer cannabis use problems than preference for hybrid species. CONCLUSIONS: Individuals who use cannabis to manage chronic pain may be at a lower risk for cannabis use problems, relative to individuals who use it for other indications, potentially as a function of their species preference.